Analisis Pengelolaan Arsip Dinamis di Dinas Perpustakaan dan Kearsipan Kabupaten Aceh Barat - Darma, Darma; Mardhiah, Nellis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is twofold namely to analizy the management of dynamic archives in the Library and Archives Office of West Aceh District and to examine the obstacles faced in the process of managing the archives. This study uses management theory by Ricky W.Griffin a research foundation. Data collection techniques were carried out by means of observation, interviews and documentation. The results of the study indicate that records management includes the creation includes incoming and outgoing mail archives. The use of archives is their use in the continuity of work and archive storage arranged according to the order of the classification code, in order to facilitate the retrieval of archives. Archive maintenance is done by cleaning the dust using a duster and mothballs. Archive depreciation has never been carried out, but there is a depreciation plan in 2023 with preparation of archive retention schedule. Dynamic archive management has obstacles including the lack of archivist functional, the absence of archive depots and record centers, the absence of an archive list, archive management that is still done manually and the limited budget.